Formulation of an accessibility indicator for sidewalk and street crossings - Keppe Junior, Celso Luiz Guimarães (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2008)
This article discusses an easy and practical way to assess the service level of public spaces (sidewalks and street crossings) intended for physically impaired individuals by creating an index that considers the most important aspects from the perspective of individuals in wheelchairs. The index is defined by identifying and ordering physical and environmental variables associated with comfort, safety, and environmental aspects. The physical and environmental variables are given different weights according to how they are viewed by wheelchair users, which defines the Sidewalk and Street Crossing Accessibility Index (or IACT in portuguese). Wheelchair users tested this index at two locations of the city of São Carlos. This tool will enable public authorities to assess the quality of public spaces within a route or in specific sections along which physically impaired individuals travel.